Estimating the economic costs of COVID-19 in Nigeria - Andam, Kwaw S.; Edeh, Hyacinth O.; Oboh, Victor; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2020)
In this paper we analyze the economic impacts of the COVID-19 pandemic and the policies adopted to curtail the spread of the disease in Nigeria. We carry out simulations using a multiplier model based on the 2018 Social Accounting Matrix (SAM) for Nigeria, which includes supply-use tables for 284 goods and services. The pandemic’s global reach and impact on the global economy combined with the response policies in Nigeria represent a large, sudden shock to the country’s economy. The SAM multiplier model is well-suited for measuring the short-term direct and indirect results of this type of shock because the SAM represents both the structure of the economy and the interactions among economic actors via commodity and factor markets. Our analysis focuses on the five-week lockdown implemented by the federal government across the Federal Capital Territory of Abuja and Lagos and Ogun states from late March to early May 2020, the federal lockdown for Kano from mid-April, and the state-level lockdowns that were implemented from mid-April for around seven weeks in Akwa Ibom, Borno, Ekiti, Kwara, Osun, Rivers, and Taraba states. We estimate that during the lockdown periods Nigeria’s GDP suffered a 34.1 percent loss due to COVID-19, amounting to USD 16 billion, with two-thirds of the losses coming from the services sector. The agriculture sector, which serves as the primary means of livelihood for most Nigerians, suffered a 13.1 percent loss in output (USD 1.2 billion). Although primary agricultural activities were excluded from the direct restrictions on economic activities imposed in the lockdown zones, the broader agri-food system was affected indirectly because of its linkages with the rest of the economy. We estimate that households lost on average 33 percent of their incomes during the period, with the heaviest losses occurring for rural non-farm and for urban households. The economic impacts of COVID-19 include a 14-percentage point temporary increase in the poverty headcount rate for Nigeria, implying that 27 million additional people fell below the poverty line during lockdown. Lastly, we consider economic recovery scenarios as the COVID-19 policies are being relaxed during the latter part of 2020. Our findings have implications for understanding the direct and indirect impacts of COVID-19, for policy design during the recovery period, and for planning future disease prevention measures while protecting livelihoods and maintaining economic growth.